Prognostic factors of gingival-alveolar squamous cell carcinoma of the maxilla. (September 2016) - Morice, A.; Ostertag, A.; Sahli-Amor, M.; Goudot, P.; Bertolus, C.; Schouman, T.
Abstract: Objectives: To determine prognostic factors in gingivo-alveolar squamous cell carcinoma of the maxilla (GA-SCC-M), and particularly the prognostic value of both vertical and antero-posterior tumor spread. Material and methods: Our retrospective study included all naïve-treatment patients treated in our center between 2006 and 2013 for GA-SCC-M. Posterior involvement was considered when the tumor extended behind the mesial side of the first maxillary molar. Spread posterior to the maxillary tuberosity was defined by the spread to at least one of the following structures: pterygomaxillary fissure, pterygoid muscles, and processes. Involvement of the maxillary sinus floor, nasal fossa, and orbital floor was assessed, concerning the vertical spread. Results: A radiological tumor spread to the nasal fossa, maxillary sinus floor, and orbital floor were prognostic factors independently of age, cervical lymph node metastasis and positive margins in multivariate analysis (p < 0.05). Radiological suggested spread tended to be noticeably more predictive of a poor prognosis than histological proven tumoral spread. The prognosis was not significantly different between clinical tumoral spread anteriorly or posteriorly to the first molar (p = 0.46). The prognosis was not worsened, even in case of radiological suggested spread posterior to the maxillary tuberosity (p = 0.09). Conclusion: A vertical radiological spread of GA-SCC-M was a prognostic factor but not the extension posteriorly to the maxillary tuberosity. T4b tumors were mostly resectable, proving that a T4b stage was not predictive of unresectability in GA-SCC-M of the maxilla.